Optimization of sand fly embryo microinjection for gene editing by CRISPR/Cas9. - Ines Martin-Martin; Azadeh Aryan; Claudio Meneses; Zach N Adelman; Eric Calvo (Public Library of Science (PLoS), 2018)
BACKGROUND:Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 technology has rapidly emerged as a very effective tool for gene editing. Although great advances on gene editing in the medical entomology field have arisen, no attempts of gene editing have been reported in sand flies, the vectors of Leishmaniasis. METHODOLOGY/PRINCIPAL FINDINGS:Here, we described a detailed protocol for sand fly embryo microinjection taking into consideration the sand fly life cycle, and manipulation and oviposition requirements of this non-model organism. Following our microinjection protocol, a hatching rate of injected embryos of 11.90%-14.22% was achieved, a rate consistent with other non-model organism dipterans such as mosquitoes. Essential factors for the adaptation of CRISPR/Cas9 technology to the sand fly field were addressed including the selection of a target gene and the design and production of sgRNA. An in vitro cleavage assay was optimized to test the activity of each sgRNA and a protocol for Streptococcus pyogenes Cas9 (spCas9) protein expression and purification was described. Relevant considerations for a successful gene editing in the sand fly such as specifics of embryology and double-stranded break DNA repair mechanisms were discussed. CONCLUSION AND SIGNIFICANCE:The step-by-step methodology reported in this article will be of significant use for setting up a sand fly embryo microinjection station for the incorporation of CRISPR/Cas9 technology in the sand fly field. Gene editing strategies used in mosquitoes and other model insects have been adapted to work with sand flies, providing the tools and relevant information for adapting gene editing techniques to the vectors of Leishmaniasis. Gene editing in sand flies will provide essential information on the biology of these vectors of medical and veterinary relevance and will rise a better understanding of vector-parasite-host interactions.